Analysis of nasal septum deviation and nasal pyramid Based on computed tomography (CT) scans - Jovanovic, Aleksandar (Medicinski podmladak, 2026)
Introduction: Among all radiological diagnostic methods for assessing nasal function, multidetector computed tomography (MDCT) of paranasal and nasal cavities has the highest sensitivity.The Aim: The aim of our research was to describe different types and types of deviation of the nasal septum and their influence on the size of nasal passages in relation to the concha and nasal mucosa, by analyzing computed tomographic (CT) images.Material and Methods: The study included 50 patients aged 21 to 65, 28 were women and 22 were men. On CT scans, we measured the flow of the nasal passages, the degree and type of the curvature of nasal septum, the size and ratio of the nasal shells in relation to the nose and their influence on the size of nasal passages, the curvature (deviation) of the cartilaginous and bony parts of the nasal septum and described their relationship and the relationship with nasal passages and nasal concha.  Results: Through our research and statistical analysis, we found there are 7 types of nose deviation 1. Deviation in the shape of the letter “C”, 2. Deviation in the shape of the letter “S”. 3. Deviation in the shape of the inverted letter “C” 4. Deviation in the shape of the letter inverted letter “S” 5. Deviation of the caudal part of the cartilaginous nasal septum in the form of a ridge, 6. Deviation in the form of a “thorn” and 7. perforated nasal septum. In 46 examinees (92% of cases) with septal deviation, we found the mucosa was more thickened and hypertrophic on the side opposite to septal deviation (p
Keywords: nasal septum deviation; CT computed tomography of the nasal pyramid; hypertrophy of the nasal mucosa